2016
DOI: 10.3389/fendo.2016.00120
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotropin Receptor Epitope and Human Leukocyte Antigen in Graves’ Disease

Abstract: Graves’ disease (GD) is an organ-specific autoimmune disease, and thyrotropin (TSH) receptor (TSHR) is a major autoantigen in this condition. Since the extracellular domain of human TSHR (TSHR-ECD) is shed into the circulation, TSHR-ECD is a preferentially immunogenic portion of TSHR. Both genetic factors and environmental factors contribute to development of GD. Inheritance of human leukocyte antigen (HLA) genes, especially HLA-DR3, is associated with GD. TSHR-ECD protein is endocytosed into antigen-presentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 105 publications
2
31
2
1
Order By: Relevance
“…And those alleles were also reported to be susceptible to rheumatoid arthritis and type 1 diabetes mellitus . The HLA‐DPB1*05:01 allele is also one of the risk alleles in Graves' disease . Therefore, those common HLA alleles seen in other autoimmune diseases suggested an existence of susceptible HLA‐associated autoimmunity in id‐IAD.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…And those alleles were also reported to be susceptible to rheumatoid arthritis and type 1 diabetes mellitus . The HLA‐DPB1*05:01 allele is also one of the risk alleles in Graves' disease . Therefore, those common HLA alleles seen in other autoimmune diseases suggested an existence of susceptible HLA‐associated autoimmunity in id‐IAD.…”
Section: Discussionmentioning
confidence: 78%
“…The most well‐known role of HLA molecule is to bind and present epitopes to pathogenic T cells . Autoantigen epitope peptides are presented with HLA on the surface of antigen‐presenting cells in autoimmune diseases. On the other hand, tumour‐associated antigen or neoantigen epitope peptides are presented in malignant diseases .…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune thyroid disease (AITD) is a thyroidspecific autoimmune disease, and Graves' disease (GD) and Hashimoto's thyroiditis (HT) are two major components of AITDs [1][2][3]. When individuals with susceptible genetic background are exposed to environmental factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…When individuals with susceptible genetic background are exposed to environmental factors (e.g. iodine, smoking, infections, stress, and trauma), AITDs may develop [1][2][3] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Twin studies have shown that 80% of the susceptibility to GD is genetic [12]. There are well-established associations between alleles of the major histocompatibility complex with GD, with susceptibility being carried with HLA-DR3 and HLA-DR4 haplotypes [13]. Other susceptibility loci at which association has been replicated include those at cytotoxic T lymphocyte antigen-4, protein tyrosine phosphatase nonreceptor-22, basic leucine zipper transcription factor 2, and CD40 [14].…”
mentioning
confidence: 99%